The Relationship between the Use of Audio-Visual Learning Media and Learning Motivation with Learning Outcomes in Elementary School - Dela Erlitaviana; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2025)
Learning media is an important aspect of learning. There are many media developments in this era, from the various learning media especially audiovisual types. This media is widely used by teachers because it is believed to have an impact in improving learning outcomes. This investigation aims to prove the relation between the use of audiovisual media and learning motivation with the learning’s outcomes of IPAS for grade V students in Gugus Diponegoro, Sigaluh District, Banjarnegara Regency. This study uses a correlational quantitative method. Sampling was taken with a purposive sampling technique which had a total sampling of 85 respondents. The result is the coefficient of determination shows (1) 0.683 there is a relationship between the use of audiovisual learning media with IPAS learning outcomes; (2) 0.721 there is a relationship between learning motivation with IPAS learning outcomes; and (3) 0.825 together there is a relationship between the use of audio- visual learning media and learning motivation with IPAS learning outcomes in Gugus Diponegoro Sigaluh District Banjarnegara Regency.